FUNCTIONAL AND SEMANTIC PROPERTIES OF COMPOUND NEOLOGISMS IN MODERN ENGLISH - Bazarov Ihtiyor Rahmatullayevich; Khudoinazarova Nargiza Khiridovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Modern English demonstrates remarkable lexical flexibility, especially in the formation of neologisms. Among the most productive types of lexical innovation are compound neologisms, which are new words created through the combination of two or more lexical stems. These formations actively reflect technological progress, economic transformation, cultural change, and digital communication. The present article examines the functional and semantic properties of compound neologisms in Modern English. Special attention is given to their nominative role, communicative economy, stylistic expressiveness, semantic transparency, metaphorization, and contextual variability. The paper also analyzes structural models of compounding and explores examples drawn from media, business, technology, and everyday discourse. The study concludes that compound neologisms represent one of the most dynamic mechanisms of vocabulary expansion in Modern English and serve as linguistic indicators of contemporary social development.